Święty Mikołaj, muchomory i maliny. Rozpoznanie narracji dotyczących ekonomii w polskich sztukach wizualnych od lat dziewięćdziesiątych do współczesności - Wiktoria Kozioł (Miejsce)
The aim of the article is to discuss economic themes in Polish visual arts after 1989. The study puts forward arguments to support the claim that economic motifs did appear in mainstream art, but were not identified. The featured attempt to arrange economic issues in a certain order consists in distinguishing three periods: 1990–2002/2003, when social distinction and consumption are thematised. Polemics against neoliberal discourse emerge (work of Jerzy Truszkowski); 2002/2003–2009/2010 – spreading of narratives that go beyond model representations of middle-class entrepreneurs (”Allocation” by Robert Rumas, among other works); 2008–2010–today – artists make use of academic theories to describe the job market situation and analogies with radical political movements (Wojciech Doroszuk, among other artists).